2011
DOI: 10.5562/cca1777
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Resolution in Capillary Electrophoresis for Protein Profiling in Identification of Genetic Modification in Foods

Abstract: Abstract. The capillary electrophoresis with UV detection was employed for protein profiling in extracts from maize and soybeans. Modifications of back-ground electrolyte and coating the capillary wall with polybrene was employed in order to decrease the protein adsorption on the capillary walls. The obtained protein profiles were compared for transgenic and non-transgenic variants, showing in some cases significant changes that might be employed for identification of genetic modifications of plants or foods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Profiling analysis of proteins has been also reviewed for the analysis of genetically modified crops . CE‐UV was employed for protein profiling in extracts from transgenic and nontransgenic variants of maize and soybeans . Some protein changes were attributed to the genetic modification; however, it was indicated that larger number of samples might be needed to obtain statistically significant results.…”
Section: Peptides and Proteinsmentioning
confidence: 99%
“…Profiling analysis of proteins has been also reviewed for the analysis of genetically modified crops . CE‐UV was employed for protein profiling in extracts from transgenic and nontransgenic variants of maize and soybeans . Some protein changes were attributed to the genetic modification; however, it was indicated that larger number of samples might be needed to obtain statistically significant results.…”
Section: Peptides and Proteinsmentioning
confidence: 99%
“…In the case of the albumins, small quantitative and qualitative differences were found between both samples indicating differences in the content of the albumin fraction of the Bt11 maize in comparison with the isogenic counterpart. In another work, Latoszek et al proposed the use of dendrimers, symmetrical macromolecules with three-dimensional structures, as pseudostationary phases in CE to decrease protein adsorption and improve resolution on the protein profiles increasing the chance of discrimination between conventional and transgenic maize [ 39 ]. Silicon-based and dendrimers with amine core were tested in different concentrations.…”
Section: Applications Of Capillary Electrophoresis (Ce) To the Stumentioning
confidence: 99%
“…To date, a wide variety of methodologies have been developed for the monitoring of GM contents, such as two-dimensional electrophoresis (Kim et al 2006 ), protein capillary electrophoresis (Latoszek et al 2011 ), HPLC (López et al 2009 ), and ELISA (Xu et al 2009 ). Of these methodologies though, polymerase chain reaction (PCR) and real-time PCR is currently the most widely applied technique owing to its high sensitivity and specificity (Marmiroli et al 2008 ) while conventional PCR methods need to handle post-PCR products for gel electrophoresis or enzymatic digestion, real-time PCR does not need post-PCR manipulations which significantly reduce the risk of laboratory contamination and is more convenient.…”
Section: Introductionmentioning
confidence: 99%